CONFLICT MANAGEMENT AND THE ROLE OF STAKEHOLDERS IN SCHOOL - Indri Wahyu Rahmadayanti; Muh Samsudin; Moh Syifa A Widigdo (JURNAL AL-TANZIM, 2021)
This study aims to analyze the role of stakeholders in conflict management in elementary schools. This type of research is descriptive qualitative research. data collection techniques using observation, interviews, and documentation. The results of the study show that there are several ways or stages that are carried out by stakeholders in conflict management. 1) planning in the form of problem identification such as knowing the form of conflict and the source of the conflict. The form of conflict that occurs in elementary schools is a form of conflict that occurs between teachers, teachers, and students, between students, and between principals and teachers. Sources of conflict occur due to differences in perception, lack of attention, miscommunication, and misunderstanding. 2) determining the approach and application of conflict management methods including conflict resolution with the compromise method; 3) Evaluation. This study implies the importance of managing conflict so that existing conflicts become a source of strength for school change and progress by community expectations.